Implementation of Character Education at the Al Ikhlas Taliwang Islamic Boarding School - Khaeru Kurniawan Putra (JURNAL PENDIDIKAN IPS, 2023)
This article discusses the implementation of character education at the Al Ikhlas Taliwang Islamic Boarding School. This research is intended to answer the problems: (1) Model of implementing character education at Al Ikhlas Taliwang Islamic Boarding School, (2) How to evaluate character education at Al Ikhlas Taliwang Islamic Boarding School. This research includes a case study using a qualitative approach. Data collection uses interview, observation and documentation methods. The data analysis techniques use the theories of Miles, Huberman, and Saldana, namely data collection, data display, data condensation, and data verification. The results of the research can be concluded: (1) The implementation of character education is aimed at forming students who have noble character and are able to adapt to the existing environment. (2) Evaluation of character education by involving existing stakeholders. From leaders, caregivers and teachers, even senior students also participated. This evaluation activity is carried out at the end of every year. As a result, several points that did not work optimally were followed up with updates to the character education implementation model for the following year.